Mercury concentrations of the EN20001_6 core segment from Lake Khamra, Yakutia, Siberia - Amelie Stieg; Jens Strauss; Justin Lindemann; Boris K Biskaborn; Ulrike Herzschuh; Izabella Baisheva; Luidmila A Pestryakova; Hanno Meyer (PANGAEA, 2025)
The data includes total mercury concentrations (THg, given in μg/kg) of 22 samples from the core segment EN20001_6. Due to limited sample material, THg concentrations were analysed on the rim material of the individual samples of EN20001_6. All measurements were carried out at AWI Potsdam. Mercury concentrations were measured with a MLS-MWS DMA-80 evo III, with a detection limit of 0.003 ng and a laboratory proven limit of determination of 0.4 ng.